Executive functions in kindergarten children at risk for developmental coordination disorder. Issue 3 (27th May 2019) - Alesi, Marianna; Pecoraro, Donatella; Pepi, Annamaria
Abstract: Executive functioning (EF) is a key cognitive process for development. Little is known about EF in Kindergarten children at risk for developmental coordination disorder (DCD), despite this age being one of the most critical and intensive period of motor and cognitive development. In our investigation we compared EF in kindergarten children at risk for DCD with Typically Developing (TD) children. Participants were 36 Italian children, 18 at risk for DCD (9 boys and 9 girls) who had a mean age of 4.6 years and 18 TD (9 boys and 9 girls) who had a mean age of 4.6. Executive functions were measured by tasks targeting cold executive functioning (working memory, fluency, inhibitory control) and two assessments of hot executive functioning (Snack Delay and Gift Wrap). Significant differences were found between children at risk for DCD and TD children on cold EF tasks of visuo-spatial working memory abilities, fluency and inhibitory control, but not on hot EF tasks. The findings suggest that it is advisable to implement preschool cognitively challenging physical activities programmes.